Molecular landscape of atherosclerotic plaque progression: insights from proteomics, single-cell transcriptomics and genomics - Chaonan Wang; Yuyao Feng; Xiaoyan Liu; Haidan Sun; Zhengguang Guo; Jiang Shao; Kang Li; Junye Chen; Keqiang Shu; Deqiang Kong; Jiaxian Wang; Yiran Li; et al. (BMC Medicine, 2025)
Abstract Backgrounds Atherosclerosis is a major contributor to cardiovascular diseases worldwide. Despite advancements in understanding its pathology, significant gaps remain in the molecular characterization of atherosclerotic plaques. This study addresses this gap by extensively profiling the proteomic landscape of carotid atherosclerotic plaques, classified under the American Heart Association (AHA) types IV to VI, to identify potential biomarkers and therapeutic targets. Methods The study employed an integrated approach using data-independent acquisition (DIA) proteomics, single-cell RNA sequencing, and Mendelian randomization (MR). A total of 87 human carotid plaques were analyzed to identify and quantify protein expression. These proteins were then mapped to specific regions within the plaques, such as the fibrous cap and lipid core, and further validated in independent samples and single-cell datasets. Furthermore, Mendelian randomization techniques were employed to assess causal relationships between identified proteins levels and ischemic stroke. Results The proteomic analysis of the 87 carotid plaques revealed 6143 proteins, highlighting diverse expression profiles across different plaque stages. Notably, proteins like CD44 and GAL-1 were predominantly expressed in the fibrous cap, suggesting a role in plaque stability, while TREM2, SMAD3, and IL-6R showed higher expression in the lipid core, indicating involvement in inflammatory processes. These findings were further corroborated by single-cell RNA sequencing, revealing cell-specific expression patterns that align with the observed proteomic data. Additionally, MR analysis indicated the causal role of IL6R, CD44, and SMAD3 in ischemic stroke. Conclusions This study provides valuable insights into the progression of atherosclerotic plaques, identifying key proteins that could serve as potential biomarkers and therapeutic targets. It enhances our molecular understanding of atherosclerosis and opens up new avenues for treatment. Additionally, our study demonstrates the accuracy and robustness of proteomics in prioritizing genes associated with plaque-related traits.